2022
DOI: 10.3390/cancers14102408
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells (CSCs), Circulating Tumor Cells (CTCs) and Their Interplay with Cancer Associated Fibroblasts (CAFs): A New World of Targets and Treatments

Abstract: The importance of defining new molecules to fight cancer is of significant interest to the scientific community. In particular, it has been shown that cancer stem cells (CSCs) are a small subpopulation of cells within tumors with capabilities of self-renewal, differentiation, and tumorigenicity; on the other side, circulating tumor cells (CTCs) seem to split away from the primary tumor and appear in the circulatory system as singular units or clusters. It is becoming more and more important to discover new bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 190 publications
0
11
0
1
Order By: Relevance
“…It is reported that CAFs can secrete various cytokines (IL-10, TGF-b, TNF, IFN-g, and IL-6) and are involved in the recruitment and maturation of macrophages, T lymphocytes, and natural killer cells, which collectively promote aggressive behavior, attenuate the response to therapy, and increase tumor cell survival (45)(46)(47). However, some studies have confirmed that immune activation of CAFs favors the availability of the tumor to immune cells and promotes antitumor immune response (48,49). The inhibitory or promoting effects of CAFs only occurred in specific differentiated cancers or at different stages of tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that CAFs can secrete various cytokines (IL-10, TGF-b, TNF, IFN-g, and IL-6) and are involved in the recruitment and maturation of macrophages, T lymphocytes, and natural killer cells, which collectively promote aggressive behavior, attenuate the response to therapy, and increase tumor cell survival (45)(46)(47). However, some studies have confirmed that immune activation of CAFs favors the availability of the tumor to immune cells and promotes antitumor immune response (48,49). The inhibitory or promoting effects of CAFs only occurred in specific differentiated cancers or at different stages of tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive liquid biopsy opens up detection possibilities for very rare circulating cancer stem cells (CSCs). CSCs and CTCs are particularly interesting targets in basic research, but also in clinical studies, due to their multiple roles and involvement in tumorigenesis, cancer progression, and resistance to therapy [ 37 , 38 , 39 ]. However, it is currently difficult to use these cells in the clinical setting: firstly, due to the lack of fully validated biomarkers, and secondly, due to the nonunique method for their identification.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Only a small proportion of tumor cells is in fact capable of inducing tumor growth when transferred to immunodeficient mice or, e.g., semi-solid media in vitro. This stem cell-like subpopulation is characterized by high proliferative potential, the capacity to self-renew and rebuild progeny [ 10 ]. Various cell surface proteins, including CD133 and CD44, have been identified as cancer stem cell markers [ 11 , 12 ].…”
Section: “Side Population” Cells In Cancermentioning
confidence: 99%
“…Various cell surface proteins, including CD133 and CD44, have been identified as cancer stem cell markers [ 11 , 12 ]. Markers that would allow for the identification and isolation from tumors of CSCs are often lacking specificity and mostly rather represent markers for stem cells in general, as is true for CD133, CD44, and the aldehyde dehydrogenase, ALDH [ 10 ]. In the absence of tumor entity-specific CSC markers, the rapid extrusion of Hoechst 33342 by ABC transporters has become an established FACS-based technique with which these CSCs (which can be defined and represented in FACS as a so-called “side population”, SP) can be quantified and enriched by “sorting”.…”
Section: “Side Population” Cells In Cancermentioning
confidence: 99%